Emulating value-chains of fast-moving consumer goods to improve uptake of co-packaged ORS and zinc for childhood diarrhoea: evaluation of the ColaLife trial. Issue 3 (6th June 2022) - Ramchandani, Rohit; Berry, Simon; Berry, Jane; Tembo, Stephen; Black, Robert E
Abstract : Introduction: Oral rehydration salts (ORS) and zinc comprise the globally recommended treatment for diarrhoea in children aged <5 years. However, limited access contributes to low uptake of this treatment and subsequently high rates of morbidity and mortality among this age group in low-income and middle-income countries. We adopted approaches used for private-sector value-chains of fast-moving consumer-goods, involving the simultaneous stimulation of supply and demand. These approaches were applied to the introduction of an innovative co-packaged diarrhoea-treatment kit (ORSZ co-pack) to increase ORS and zinc coverage at the community level in Zambia. Methods: We tested our approach using an observational pre–post test study design in two intervention districts in rural Zambia (Kalomo and Katete), each with a matched comparator (Monze and Petauke, respectively). We assessed the effect on coverage, of ORS and zinc as well as ORS alone, by conducting household surveys of a total of 2458 and 2477 caregivers of children aged <5 years at baseline and endline, respectively, across the four districts. We also assessed whether the source of ORS (public or private sector) changed following the intervention. Results: Both intervention districts experienced significant increases in coverage of ORS and zinc from <1% at baseline to 46.9% and 46.3% in Kalomo and Katete, respectively. Uptake in the comparator districts remained low at 1.7% and 0.6% in Monze and Petauke, respectively. For the secondary outcome examining ORS coverage (with or without zinc), the intervention was associated with a significant increase in Kalomo versus Monze, but not in Katete versus Petauke. There was a clear shift from the public to the private sector, and specifically to the use of the ORSZ co-pack. Conclusion: Implementation of a value-chain creation approach for an innovative, over-the-counter, co-packaged diarrhoea-treatment kit can significantly improve the coverage of ORS and zinc.